A mudança do perfil do público da EJA: desafios e perspectivas - Corte, Luciane Cristina (2016)
This Dissertation has the theme Youth and Adult Education (EJA) in Primary Education II studies and an Integrated Centre for Youth and Adult Education (CIEJA) located in São Paulo. To understand its purpose: a change of the EJA public profile, with clipping about the inclusion of young people in their first job, starting from the theoretical framework of critical theory of Frankfurt in dialogue with Paulo Freire and other authors who deal with this issue, presents research issues that question the subject: What factors contribute to the change of the EJA public profile (especially age) in the last ten years? What is the importance of this mode of education in socio-professional insertion of the young? What training opportunities are possible in the context pointed? Students of IV modules (their 8th and 9th grades) aged between 15 and 18 years will be heard through oral life story narratives to prove or disprove the hypothesis that answer these questions. The first hypothesis assumes that the factors contributing to the change in the age profile of the public especially the EJA have been: the dissemination of projects and public programs of Youth and Adult Education; the increase in years of compulsory permanence in school; schooling right expectations for all determined by the LDB and subsequent standardization; dropout and repetition of young people and teenagers in mainstream education; the need to accelerate the studies of these young people for entering the labor market. The second hypothesis suggests that the young person does not receive training and tools necessary to face the demands and contradictions of this social model that determines the youth of low income (for their insertion in the labor market), only the areas of providing poor service and he, not being formed to have a critical reading of reality and lie therein shall be subject to such working conditions, living up, in most cases, no more than twice the minimum wage. In this perspective, the school has the role only to mold him to receive orders and be obedient to the rules that culminate with the needs of the contemporary capitalism imposes, not contributing to the emancipation of their conditions of life and work. The third hypothesis indicates that in serving the diverse audience of EJA are not established, effectively, the relationship between education and work. The objectives are: to identify the main factors influencing the change in the profile of EJA in the last 10 years; verify the contributions of EJA for the inclusion of youth in the labor market, specifically the first job and think about training practices to meet the increasingly diverse audience that attends. The empirical research methodology includes desk research and literature plus the history of life theme. The use of life history method constituted material for analysis, determining the following categories: discursive fragmentation and shallow thinking; linkages apparently superfluous; contradiction between the real and the possible; Rushing to complete schooling and pseudo-formation. From the analysis of the content of oral narratives of life story, it was found that the hypotheses are confirmed and the results showed that there are contradictions to be overcome for a better articulation between the training undertaken in EJA and the world of work.